A transformação digital na aquicultura: um framework para a digitalização da piscicultura - Aschidamini, Pedro Henrique Benin (2024)
In the last decade, a wave of technological applications has gained prominence following the emergence of the Industry 4.0 (I4.0) model, which is related to information and communication technology (ICT). Branches of the model have been adapting to various fields, such as the digital transformation process, with increasing emphasis on agriculture and, consequently, aquaculture. Since the turn of the century, the global average growth rate of aquaculture has been 5.3% per year, and the estimated increase in fish production by 2030 is 15%. Due to this growth, I4.0 technologies are being applied in aquaculture, potentially revolutionizing the production process, known as Aquaculture 4.0. However, the term Aquaculture 4.0 is still imprecise, and the application of I4.0 technologies does not have a specific architecture for the field of aquaculture. Based on these concepts, this research explores ICT applied to aquaculture, providing a framework for digitization and data use in fish farming. To conduct the research, the Process Approach (also known as the Cambridge Approach) was used, carried out in four stages: (i) The first stage is a systematic literature review (SLR), using the Proknow-C method (Knowledge Development Process - Constructivist). (ii) The second stage is a textual analysis exploring the scientific base resulting from the SLR to construct the digital technologies framework based on the Industry 4.0 model. (iii) The third stage is an exploratory field research with semi-structured interviews with experts from agribusiness, aquaculture, and industry to validate the developed framework. (iv) The fourth and final stage is a qualitative analysis of the use of an experimental technology built based on the developed framework through a Proof of Concept (PoC). As results, the first stage yielded a bibliographic portfolio with 54 articles. The technologies applied in aquaculture were identified and segmented according to the Industry 4.0 model, classified into technologies related to action, observation, interpretation, and decision, divided into five technological axes: Monitoring, IoT, Automation, Decision, and Hardware/Laser. The results of the first stage served as a basis for the second stage of the research, which resulted in the framework based on the formulated literature base. In the third stage, 13 experts were interviewed who validated the framework, defined in five axes: (i) Organizational, (ii) Sustainability, (iii) Technological Infrastructure, (iv) Data Collection, (v) Smart Aquaculture Farms. In the fourth stage, the PoC was carried out with two fish farmers, in which the use of the framework for digitization proved viable. Finally, the difficulties of implementing digital technology were analyzed in terms of feasibility, usability, and utility for the aquaculture producer and developers of digital technologies. The research objectives were achieved, and the research question was answered. The digitalization process in fish farming should be carried out following the steps of each axis described in the developed framework. It is proposed as a continuation of the research to conduct animal welfare analyses using digital technologies, and to carry out quantitative analyses of economic results from the use of digital technologies in aquaculture farms.